Determinants of Continuance Intention to Use Mobile Commerce during the Emergence of COVID-19 in Indonesia: DeLone and McLean Perspective - Dhiona Ayu Nani; Lia Febria Lina (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
The level of online shopping in Indonesia has been increasing since its inception, especially due to the COVID-19 pandemic which has caused a more significant increase. In addition to the quality of supporting applications, service quality in the form of timeliness in delivery and suitability of goods ordered by consumers are also important aspects that need to be considered by businesses that use the Electronic Commerce (E-commerce) platform. This study aims to examine the effect of system quality, information quality, and reliability on user satisfaction of Mobile Commerce (M-commerce), the effect of user satisfaction on the intention to use M-commerce continually, and the role of user experience in strengthening the relationship between user satisfaction and intention to use M-Commerce continually. We used 196 M-commerce consumers who conducted online shopping within three months (April-June 2020) as samples. Hypothesis was tested using PLS-SEM. The findings prove that customer satisfaction is not only determined by technological factors such as system quality, but also customer value, such as service accuracy in delivering products. Furthermore, this study has a practical contribution whether understanding individual behavior in M-commerce adoption can be an effective tool to help decision makers develop superior strategies to compete in the digital era and can be used to make policies.